Plasmid curing pattern of nosocomial pathogens of intensive care units (ICU) in Zagazig University Hospital - El Salam, Soheir; Ghaly, Mohammed Farouk; Shahen, Ahmed Anwar; Amer, Mahmoud Mostafa; Abdelkader, Sanaa Atef (Asian Journal of Medical and Biological Research, 2017)
Nosocomial infections and antibiotic resistance are serious and growing phenomenon in contemporary medicine and has emerged as one of the public health concerns. A total of seventy isolates of bacteria were collected from patients. The selected isolates include 33 (56.9%) from males and 25 (43.1%) from females. All bacteria were susceptible to imipenem followed by amikacin, ceftazidime, ciprofloxacin and tobramycin, respectively. The multi-drug resistant (MDR) bacterial isolates (33 isolates) divided into four groups named Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus were selected to be identified according to the keys of different identification protocols. Escherichia coli found to be the most frequent pathogen within MDR isolates followed by Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella pneumonia, respectively. The MICs and MBCs of (Imipenem, Amikacin, Ceftazidime and ciprofloxacin) against the most resistant isolates were determined. Generally, P. aeruginosa (Strain No. 55) was found to be the highest resistant bacteria. Plasmid profile of Pseudomonas aeruginosa was carried out, after incubation at 37oc for 24hr recorded no changes in plasmid and compared with incubation at 43oc (plasmid curing) which showed complete removal of plasmid bands and the tested bacteria became more sensitive to antibiotics. This study therefore determined the prevalence, anti-biotic susceptibility and plasmid patterns of P. aeruginosa strains from clinical specimens obtained from the intensive care units of Zagazig University Hospital in Egypt. Asian J. Med. Biol. Res. December 2016, 2(4): 703-711